An integrated approach for understanding the factors that facilitate or constrain the adoption of soil carbon enhancing practices in East Africa, specifically Western Kenya - Karanja Ng'ang'a, Stanley; George Magambo, Kanyenji; Anyango Jalang'o, Dorcas; Nguru, Wilson Maina; Girvetz, Evan Hartunian (International Center for Tropical Agriculture, 2019)
The survey data on soil carbon enhancing practices in western Kenya is systematically organized in Microsoft Excel tables. The data entails general household characteristics, plot characteristics, practices implemented, yield, inputs, livestock ownership, social capital, access to credit, access to extension services and sources of income.